2019
DOI: 10.1103/physreve.100.042415
|View full text |Cite
|
Sign up to set email alerts
|

Persistent exclusion processes: Inertia, drift, mixing, and correlation

Abstract: In many biological systems, motile agents exhibit random motion with short-term directional persistence, together with crowding effects arising from spatial exclusion. We formulate and study a class of lattice-based models for multiple walkers with motion persistence and spatial exclusion in one and two dimensions, and use a mean-field approximation to investigate relevant populationlevel partial differential equations in the continuum limit. We show that this model of a persistent exclusion process is in gene… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Perhaps the simplest interaction is hard-core exclusion, which in passive (equilibrium) systems serves only to reduce the volume available to particles to explore: the statistical weights of the accessible microstates remain unchanged. By contrast, a hard-core repulsion between persistent particles induces an effective attraction [36] which can lead to particles clustering [37][38][39][40][41], consistent with the prediction of motility-induced phase separation [42].…”
Section: Introductionsupporting
confidence: 80%
“…Perhaps the simplest interaction is hard-core exclusion, which in passive (equilibrium) systems serves only to reduce the volume available to particles to explore: the statistical weights of the accessible microstates remain unchanged. By contrast, a hard-core repulsion between persistent particles induces an effective attraction [36] which can lead to particles clustering [37][38][39][40][41], consistent with the prediction of motility-induced phase separation [42].…”
Section: Introductionsupporting
confidence: 80%
“…We consider specifically the case of hard-core exclusion, which we implement by placing the particles on a hypercubic lattice in d dimensions, and disallow any hops that would lead to two particles occupying the same site. This model (and variants with a softer exclusion constraint) has been studied from a variety of viewpoints [7,[14][15][16][17][18][19][20][21] and is sometimes referred to as a persistent exclusion process. Macroscopically, it is expected to exhibit a motility-induced phase separation [22], which arises generically in active particle systems from a feedback between particles accumulating where the propulsion speed is low and this speed decreasing due to crowding from nearby particles.…”
Section: Introductionmentioning
confidence: 99%
“…Techniques from spatial statistics, such as the pair correlation function, are increasingly being applied to agent-based processes [54,[63][64][65][66][67][68][69][70][71][72][73]. Our approach employs a novel combination of both spatial statistics and functional data analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent results have demonstrated that drift-diffusion PDEs can be produced to approximate the evolution of agent-based processes exhibiting bias and persistence in the setting of modelling bacterial chemotaxis [74]. In addition, drift-diffusion type PDEs can be produced to approximate the evolution of a lattice-based agent-based process that includes bias, persistence, and exclusion, with the drift and diffusion terms being dependent on agent density [72]. Determining whether our approach can royalsocietypublishing.org/journal/rsif J. R. Soc.…”
Section: Discussionmentioning
confidence: 99%